Effect of organic additives on in vitro seed germination of Borneo’s endemic orchid, phalaenopsis bellina and seedling growth of vanda dearei - Cynthia Keranti, anak Kamar (Universiti Malaysia Sarawak (UNIMAS), 2015)
Orchids are one of the magnificent flowers in the world. There are diverse collections of orchids in Borneo. Phalaenopsis and Vanda species are among the beautiful species of orchid that are endemic to Borneo. Phalaenopsis bellina and Vanda dearei are wild orchids in Borneo. Only a small percentage of seeds that has been released will grow into adult plants. Therefore, in vitro micropropagation has been applied to save and mass produce of both species. The aim of the study was to determine the effect of organic additives on in vitro seed germination of Phalaenopsis bellina and the seedling growth of Vanda dearei from protocorm. Seeds of Phalaenopsis bellina from mature capsule and protocorms of Vanda dearei induced from in vitro seed cultured were used in this study. The seeds of Phalaenopsis bellina were cultured on half strength of Murashige and Skoog (1/2MS) medium with 4 types of organic additives at different concentrations. Organic additives used were tomato homogenate, potato homogenate, banana pulp, and coconut water. Control treatment was prepared in the absence of organic additives. The effects of different concentrations of each organic additive on seed germination of Phalaenopsis bellina were examined by observing the stages of seed. There were no sign of seed germination of Phalaenopsis bellina with ½ MS as a basal media and supplemented with organic additives. The protocorms of Vanda dearei were cultured on 3 types of basal media which included Murashige and Skoog (MS), half strength of Murashige and Skoog (1/2MS), and Gamborg (B5) medium. The effects of types of basal media were investigated by observing the number of protocorms that produce leaves and roots. The result obtained that B5 medium recorded the highest percentage of protocorm producing leaves (97.25%) and roots (8.33%) followed by ½ MS and MS. As the effective basal media for seedling growth of Vanda dearei were B5 and ½ MS, the effect of organic additives at different concentration were investigate with these two basal media. Types of organic additives used were banana pulp and potato homogenate. The results obtained that potato homogenate with ½ MS recorded the highest percentage of protocorm producing leaves and roots.